2020
DOI: 10.1002/adom.202001072
|View full text |Cite
|
Sign up to set email alerts
|

Lead‐Free Cs3Sb2Br9 Single Crystals for High Performance Narrowband Photodetector

Abstract: Photodetectors (PDs), converting incident photons into electrical signals, play a crucial role in modern optoelectronic applications such as photo detection, optical communications, and imaging. [1-7] Owing to high material quality, broad chemical tunability, long carrier diffusion lengths, and high mobility, Pb based metal halide crystalline perovskites have attracted great attention for sensitive PD applications. [8-11] Despite their striking advances, the toxicity of Pb and stability issues have severely li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…Figure 4f schematically illustrates a phototransistor based on a lead‐free Cs 3 Sb 2 Br 9 nanosheet at 480 nm with responsivity of 2.29 A W −1 , EQE of 1.8 × 10 3 %, and D * of 3.77 × 10 12 Jones made by Liu et al. [ 59 ] Under a bias of 6 V, they plotted the function relationship between the EQE and the wavelength as shown in Figure 4g. In particular, a maximum value was noticed at peak position of 480 nm and the corresponding full width at half maximum is 15 nm, which indicates the narrowband photoresponse in this photodetector.…”
Section: Photodetectors Based On Single 2d Materialsmentioning
confidence: 99%
“…Figure 4f schematically illustrates a phototransistor based on a lead‐free Cs 3 Sb 2 Br 9 nanosheet at 480 nm with responsivity of 2.29 A W −1 , EQE of 1.8 × 10 3 %, and D * of 3.77 × 10 12 Jones made by Liu et al. [ 59 ] Under a bias of 6 V, they plotted the function relationship between the EQE and the wavelength as shown in Figure 4g. In particular, a maximum value was noticed at peak position of 480 nm and the corresponding full width at half maximum is 15 nm, which indicates the narrowband photoresponse in this photodetector.…”
Section: Photodetectors Based On Single 2d Materialsmentioning
confidence: 99%
“…[ 33,102,106 ] Wei and co‐workers reported a narrowband photodetector based on 2D hexagonal Cs 3 Sb 2 Br 9 single crystals. [ 79 ] Figure 17h displays the EQE values of the devices at different wavelengths. The results demonstrated that a high EQE of 1.8 × 10 5 % located at 480 nm with a narrow distribution, implying the narrowband response of the devices.…”
Section: Applications Of Ilfp Single Crystalsmentioning
confidence: 99%
“…[29,42,43] Moreover, while the adoption of X − = Br − or Cl − allows the formation of a 2D structure, the corresponding bandgap is too large for visiblelight detection. [40,[44][45][46][47][48] More generally, the external quantum efficiencies (EQEs) of A 3 M 2 X 9 photodetectors operated in self-powered mode have been rather modest, typically in the range of ≈0.5-5% (i.e., much lower compared to lead-halide perovskite photodetectors). [48][49][50] 0D/2D bismuth-based PIMs have also delivered comparatively low EQEs in self-powered mode.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50] 0D/2D bismuth-based PIMs have also delivered comparatively low EQEs in self-powered mode. [51,52] Therefore, it is not surprising that most photodetector studies to date featuring antimony-and bismuthbased PIMs have resorted to operation with an applied bias voltage, [38][39][40][44][45][46][47][53][54][55][56][57][58] as that can generally mitigate the effects of an inefficient photoconversion process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation